Case reportEpidural haematoma after epidural catheter removal under multiple anticoagulant therapy: report of two cases - Pandazi, Ageliki; Karamanis, Periandros; Matsota, Paraskevi; Kontogiannopoulou, Stella; Soultanis, Kostantinos; Kostopanagiotou, Georgia (Archives of Medical Science, 2010)
We report two cases of epidural haematoma that probably developed after removal of the epidural catheter in patients receiving multiple anticoagulant and antiplatelet therapy. The first case is a 77-year-old male patient who underwent femoropopliteal artery bypass grafting surgery. The second case is a 77-year-old woman who underwent a semi-total replacement of the right hip, three days after she had a subtrochanteric fracture. Emergency laminectomy was performed in both patients but none experienced a full recovery.